Implementasi Pendekatan Deep Learning Berbasis Model Project Based Learning dalam Pembelajaran Teks Biografi Siswa Kelas X SMA Negeri 6 Solok Selatan - Aulia Sari, Liana; Zulfikarni; Afnita; Nofrahadi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the planning, implementation, and evaluation of Biography Text learning in the application of a deep learning approach based on the Project Based Learning (PjBL) model for class X students of SMA Negeri 6 Solok Selatan. The method used is qualitative research with descriptive methods. Data and research data sources were obtained through documentation results (teaching modules and other tools), observations (learning observations), interviews (Curriculum Vice and Indonesian Language teachers), and student response questionnaires. Data validation techniques were carried out through triangulation techniques (cross checks). The results of the study indicate that the implementation of the deep learning approach based on the PjBL model has been carried out very well, starting from the planning shown through the preparation of complete learning tools and the integration of PjBL syntax and deep learning principles. The implementation of student-centered learning through project-based introductory, core, and closing stages, and evaluation using authentic assessments that include diagnostic, formative, and summative. The results of the questionnaire showed a very positive student response, marked by increased motivation, understanding of the material, the creation of enjoyable learning (joyful learning), and the development of critical thinking skills through the pillars of mindful learning. However, this study identified a challenge in the form of a lack of student engagement in group activities, necessitating more optimal learning management to ensure more equitable student participation. This study recommends the use of a deep learning approach based on the Project-Based Learning (PjBL) model as an effective, innovative strategy for creating more meaningful and active Indonesian language learning at the high school level.